The gut microbiome: an orchestrator of xenobiotic metabolism - Stephanie L. Collins; Andrew D. Patterson (Elsevier, 2020)
Microbes inhabiting the intestinal tract of humans represent a site for xenobiotic metabolism. The gut microbiome, the collection of microorganisms in the gastrointestinal tract, can alter the metabolic outcome of pharmaceuticals, environmental toxicants, and heavy metals, thereby changing their pharmacokinetics. Direct chemical modification of xenobiotics by the gut microbiome, either through the intestinal tract or re-entering the gut via enterohepatic circulation, can lead to increased metabolism or bioactivation, depending on the enzymatic activity within the microbial niche. Unique enzymes encoded within the microbiome include those that reverse the modifications imparted by host detoxification pathways. Additionally, the microbiome can limit xenobiotic absorption in the small intestine by increasing the expression of cell-cell adhesion proteins, supporting the protective mucosal layer, and/or directly sequestering chemicals. Lastly, host gene expression is regulated by the microbiome, including CYP450s, multi-drug resistance proteins, and the transcription factors that regulate them. While the microbiome affects the host and pharmacokinetics of the xenobiotic, xenobiotics can also influence the viability and metabolism of the microbiome. Our understanding of the complex interconnectedness between host, microbiome, and metabolism will advance with new modeling systems, technology development and refinement, and mechanistic studies focused on the contribution of human and microbial metabolism. Key words: Gut microbiome, Xenobiotic metabolism, Absorption, Gastrointestinal tract, Pharmacokinetics, Enterohepatic circulation, Bioactivation